The development and construct validation of the mathematics proficiency test for 14-year-old students - Khairani, Ahmad Zamri; Nordin, Mohamad Sahari (2011)
Mathematics education of yesterday, where the emphasis of procedural rote learning took centre stage, is no longer viable. Today, students must understand the Mathematics that they are learning; that is, Mathematics involves various components or strands that are interdependent and interwoven. The purpose of this study was to assess three of the strands, namely, conceptual understanding, procedural fluency, and strategic competence among 14-year-old students. This study also sought empirical evidence for how the Mathematics proficiency construct contributed to each strand. Results from Rasch Model calibration showed that students were most proficient in conceptual understanding followed by strategic competence and procedural fluency. Confirmatory factor analysis confirmed that Mathematics proficiency was a significant determinant for each strand. Lastly, this study reported several implications calling for future research.